R-T-B magnet diffusion source, R-T-B magnet material and preparation method and application of R-T-B magnet material
By using non-rare earth metal elements to replace some rare earth elements in R-T-B magnet materials, the R-T-B magnet diffusion source is prepared, which solves the problems of insufficient coercive force enhancement and low utilization of rare earth elements in the prior art, and achieves the effect of significantly improving the coercive force and utilization of rare earth elements.
Patent Information
- Application Number
- CN202411997403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the coercive force increase of R-T-B magnet materials is insufficient and the utilization rate of rare earth elements is not high, making it difficult to meet the application needs of certain special fields.
A non-rare earth metal element is used instead of some rare earth elements to prepare an R-T-B magnet diffusion source, which includes alloy RaMb, R is a rare earth element, and M is a non-rare earth metal element, such as at least two of Al, Cu, Ga, Zr, Ti and Co., through which grain boundary diffusion treatment is performed to improve magnet performance.
It effectively improves the coercive force of R-T-B magnet material, and at the same time improves the utilization rate of rare earth elements, maintains a high residual magnetism, and has better temperature stability.
Smart Images

Figure CN119811882A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an RTB magnet diffusion source, an RTB magnet material and a preparation method and application thereof. Background Art
[0002] NdFeB magnets are widely used in wind power generation, electronic communications, and new energy vehicles due to their excellent magnetic energy density. However, they still have defects such as insufficient improvement in coercivity, which limits their application in some special fields. At present, the main methods to improve the performance of sintered NdFeB magnets are alloying, grain refinement, and grain boundary diffusion. Among them, the grain boundary diffusion method refers to depositing a layer of rare earth powder on the surface of the magnet by sputtering, vapor deposition, electrophoresis, coating, etc., diffusing the rare earth elements on the surface of the magnet into the interior of the magnet through heat treatment, and forming a magnetic hardening shell layer in the boundary layer of the main phase grains to improve the coercivity, but the degree of improvement is still limited, and the utilization rate of rare earth elements is not high.
[0003] Therefore, how to improve the utilization rate of rare earth elements and the coercive force of magnets is one of the issues that more and more scholars are concerned about. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects of the prior art that the utilization rate of rare earth elements in the diffusion source is low and it is difficult to significantly improve the coercive force of the RTB magnet material, and provide an RTB magnet diffusion source, RTB magnet material and its preparation method and application. The diffusion source in the present invention uses non-rare earth metal elements to replace part of the rare earth elements, which can effectively improve the utilization rate of the rare earth elements. The RTB magnet material prepared by using the diffusion source can more significantly improve the coercive force of the NdFeB magnet material while maintaining a relatively high remanence.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The present invention provides an RTB diffusion source, which comprises an alloy R a M b , R is a rare earth element; M is a non-rare earth metal element, M includes at least two of Al, Cu, Ga, Zr, Ti and Co; a and b are the mass percentages of the corresponding elements, a=40-90wt%, b=10-60wt%.
[0007] In the present invention, the R may be a heavy rare earth element and / or a light rare earth element, for example, a heavy rare earth element and a light rare earth element.
[0008] The heavy rare earth element is preferably Dy and / or Tb, such as Dy and Tb. The light rare earth element is preferably one or more of Pr, Nd and Ce, such as Ce, Nd or Pr.
[0009] When Dy is included in the R, the content of Dy is preferably 30-80 wt.%, such as 40 wt.%, 50 wt.%, 60 wt.% or 70 wt.%.
[0010] When Tb is included in the R, the content of Tb is preferably 50-80 wt.%, such as 60 wt.% or 70 wt.%.
[0011] When the R includes Pr, the content of Pr is preferably 10-50 wt.%, such as 20 wt.%, 30 wt.% or 40 wt.%.
[0012] When Nd is included in the R, the content of Nd is preferably 5-20 wt.%, such as 10 wt.% or 15 wt.%.
[0013] When Ce is included in the R, the content of Ce is preferably 10-30 wt.%, such as 20 wt%.
[0014] In the present invention, the R preferably satisfies one of the following: ① Ce and Tb; ② Pr and Tb; ③ Tb; ④ Nd and Dy.
[0015] Wherein, when the R is Ce and Tb, the mass ratio of Ce to Tb is preferably 1:(2-4), for example, 1:3.
[0016] Wherein, when the R is Pr and Tb, the mass ratio of Pr to Tb is preferably 3:(4-6), such as 3:5.
[0017] Wherein, when the R is Nd and Dy, the mass ratio of Nd to Dy is preferably 1:(6-8), for example 1:7.
[0018] In the present invention, the M is preferably Co and Cu; Cu and Ga; Co, Cu and Ga; or Cu and Al.
[0019] Wherein, when the M is Cu and Co, the mass ratio of Cu to Co is preferably 1:(0.5-1.5), more preferably 1:(0.8-1.2), for example 1:1.
[0020] Wherein, when the M is Cu and Ga, the mass ratio of Cu to Ga is preferably 1:
[0021] (0.5-1.5), more preferably 1:(0.8-1.2), for example 1:1.
[0022] Among them, when the M is Co, Cu and Ga, the mass ratio of Co, Cu and Ga is preferably (1-3): (1-3): 1, more preferably (1.5-2.5): (1.5-2.5): 1, for example 1:1:2.
[0023] Wherein, when the M is Cu and Al, the mass ratio of Cu to Al is preferably 1:(0.5-1.5), more preferably 1:(0.8-1.2), for example 1:1.
[0024] In the present invention, when the M includes Al, the content of Al is preferably 5-30 wt.%, such as 10 wt.%.
[0025] In the present invention, when M includes Cu, the content of Cu is preferably 5-30 wt.%, such as 10 wt.% or 20 wt.%.
[0026] In the present invention, when Ga is included in the M, the content of Ga is preferably 5-30 wt.%, such as 10 wt.% or 20 wt.%.
[0027] In the present invention, when the M includes Co, the content of Co is preferably 5-30 wt.%, such as 10 wt.% or 20 wt.%.
[0028] The above wt.% represents the percentage of the mass of each element to the total mass of the RTB magnet diffusion source.
[0029] In the present invention, the a is preferably 60-80wt%, such as 70wt%.
[0030] In the present invention, the b is preferably 20-50wt%, such as 30wt% or 40wt%.
[0031] In a specific embodiment, the composition of the RTB magnet diffusion source is 20 wt% Ce, 60 wt% Tb, 10 wt% Cu and 10 wt% Co, where wt% represents the percentage of the mass of each component to the total mass of the RTB magnet diffusion source.
[0032] In a specific embodiment, the composition of the RTB magnet diffusion source is 30 wt% Pr, 50 wt% Tb, 10 wt% Cu and 10 wt% Ga, where wt% represents the percentage of the mass of each component to the total mass of the RTB magnet diffusion source.
[0033] In a specific embodiment, the composition of the RTB magnet diffusion source is 80 wt % Tb, 10 wt % Al and 10 wt % Cu, where wt % represents the percentage of the mass of each component to the total mass of the RTB magnet diffusion source.
[0034] In a specific embodiment, the composition of the RTB magnet diffusion source is 60wt% Tb, 10wt% Co, 10wt% Cu and 20wt% Ga, where wt% represents the percentage of the mass of each component to the total mass of the RTB magnet diffusion source.
[0035] In a specific embodiment, the composition of the RTB magnet diffusion source is 80 wt % Dy, 10 wt % Al and 10 wt % Cu, where wt % represents the percentage of the mass of each component to the total mass of the RTB magnet diffusion source.
[0036] In a specific embodiment, the composition of the RTB magnet diffusion source is Nd 10wt%, Dy 70wt%, Al 10wt% and Cu 10wt%, where wt% represents the percentage of the mass of each component to the total mass of the RTB magnet diffusion source.
[0037] The present invention also provides an RTB magnet material, which includes a NdFeB main phase and a Nd-rich phase;
[0038] Wherein, the main phase of NdFeB includes rare earth elements and non-rare earth elements; the mass percentage of the rare earth elements is 28.5-34.5wt.%; the mass percentage of the non-rare earth elements is 1.0-2.5wt.%; the non-rare earth elements include at least two of Al, Cu, Ga, Zr, Ti and Co;
[0039] Among them, the main phase of NdFeB has a three-shell core structure, which includes an inner core and a shell covering the inner core; the inner core includes main phase grains; the shell layer includes a first shell layer, a second shell layer and a third shell layer in sequence along the direction away from the inner core; the shell layer includes a first shell layer, a second shell layer and a third shell layer in sequence along the direction away from the inner core; the concentration of rare earth elements in the second shell layer is greater than the concentration of rare earth elements in the third shell layer and is greater than the concentration of rare earth elements in the first shell layer; the concentration of non-rare earth elements in the third shell layer is greater than the concentration of non-rare earth elements in the second shell layer and is greater than the concentration of non-rare earth elements in the first shell layer.
[0040] In the present invention, the definition of "RTB" may be conventional in the art, that is, it refers to a type of magnetic material including at least rare earth elements, iron elements and boron elements and inevitable impurities.
[0041] In the present invention, the inventors discovered during the research and development process that when there are at least two non-rare earth elements, and the diffusion source formed by the cooperation of the rare earth elements and the RTB magnet substrate are subjected to diffusion treatment, the RTB magnet material obtained can form a special three-shell core structure.
[0042] In the present invention, the mass percentage of the rare earth element is preferably 30.0-32.5wt%, for example, 32.23wt%, 31.58wt%, 31.44wt%, 31.34wt%, 31.33wt% or 31.07wt%.
[0043] In the present invention, the mass percentage of the non-rare earth element is preferably 1.20-2.30wt%, such as 1.99wt%, 1.55wt%, 1.37wt%, 1.32wt% or 1.403wt%.
[0044] In the present invention, the thickness of the shell layer preferably satisfies the following relationship: the second shell layer>the first shell layer or the third shell layer.
[0045] In the present invention, the thickness of the first shell layer may be 0.1-2 μm, preferably 0.5-1.5 μm, such as 0.83, 0.65 or 0.80 μm.
[0046] In the present invention, the thickness of the second shell layer may be 0.5-5 μm, preferably 1-3 μm, such as 2.36, 2.155 or 1.19 μm.
[0047] In the present invention, the thickness of the third shell layer may be 0.2-5 μm, preferably 0.4-2.0 μm, such as 1.375, 1.53 or 0.46 μm.
[0048] In the present invention, the particle size of the NdFeB main phase may be 5-15 μm, such as 5.67, 11.1 or 14.8 μm.
[0049] In the present invention, the rare earth element is preferably a heavy rare earth element and / or a light rare earth element. The heavy rare earth element is preferably Dy and / or Tb. The light rare earth element is preferably one or more of Pr, Nd and Ce, such as Ce, Nd or Pr.
[0050] In the present invention, the rare earth element preferably satisfies one of the following: ① Ce and Tb; ② Pr and Tb; ③ Tb; ④ Nd and Dy.
[0051] In the present invention, the concentration of rare earth elements in the main phase grains may be 22-27wt%, preferably 25-26wt%, for example 25.8wt%. The concentration of rare earth elements in the first shell layer may be 22-27wt%, preferably 23-25wt%, for example 24.1wt%. The concentration of rare earth elements in the second shell layer may be 22-27wt%, preferably 23-25wt%, for example 24.5wt%. The concentration of rare earth elements in the third shell layer may be 22-27wt%, preferably 23-25wt%, for example 24.4wt%.
[0052] In the present invention, when the NdFeB main phase includes heavy rare earth, the concentration of heavy rare earth in the main phase grains may be 0.05-0.15wt%, preferably 0.08-0.12wt%, for example 0.10wt%. The concentration of heavy rare earth in the first shell layer may be 1-20wt%, preferably 1.5-1.8wt%, for example 1.7wt%. The concentration of heavy rare earth in the second shell layer may be 5-30wt%, preferably 10.5-12.0wt%, for example 10.9wt%. The concentration of heavy rare earth in the third shell layer may be 1-20wt%, preferably 3-6wt%, for example 5.5wt%.
[0053] In the present invention, when the NdFeB main phase includes light rare earth, the concentration of light rare earth in the main phase grains may be 20-30wt%, preferably 23-28wt%, for example 25.7wt%. The concentration of light rare earth in the first shell layer may be 5-30wt%, preferably 20-28wt%, for example 22.4wt%. The concentration of light rare earth in the second shell layer may be 5-20wt%, preferably 10-20wt%, for example 13.6wt%. The concentration of light rare earth in the third shell layer may be 5-30wt%, preferably 10-20wt%, for example 18.9wt%.
[0054] When the main phase grains include Pr, the concentration of Pr may be 1-10wt%, preferably 4-8wt%, such as 5.4wt%. The concentration of Pr represents the percentage of the weight of Pr to the total weight of the main phase grains.
[0055] When the main phase grains include Nd, the concentration of Nd may be 5-30wt%, preferably 20-28wt%, such as 20.3wt%. The concentration of Nd represents the percentage of the weight of Nd to the total weight of the main phase grains.
[0056] When the main phase grains include Tb, the concentration of Tb may be 0.05-0.15wt%, preferably 0.08-0.12wt%, such as 0.10wt%. The concentration of Tb represents the percentage of the weight of Tb to the total weight of the main phase grains.
[0057] When the first shell layer includes Pr, the concentration of Pr may be 1-10wt%, preferably 4-8wt%, such as 5.5wt%. The concentration of Pr represents the percentage of the weight of Pr to the total weight of the first shell layer.
[0058] When the first shell layer includes Nd, the concentration of Nd may be 5-30wt%, preferably 10-20wt%, for example 16.9wt%. The concentration of Nd indicates the percentage of the weight of Nd to the total weight of the first shell layer.
[0059] When the first shell layer includes Tb, the concentration of Tb may be 1-20wt%, preferably 1.5-1.8wt%, such as 1.7wt%. The concentration of Tb represents the percentage of the weight of Tb to the total weight of the first shell layer.
[0060] When the second shell layer includes Pr, the concentration of Pr may be 1-10wt%, preferably 5-9wt%, such as 5.4wt%. The concentration of Pr indicates the percentage of the weight of Pr to the total weight of the second shell layer.
[0061] When the second shell layer includes Nd, the concentration of Nd may be 1-10wt%, preferably 5-9wt%, for example 8.2wt%. The concentration of Nd indicates the percentage of the weight of Nd to the total weight of the second shell layer.
[0062] When the second shell layer includes Tb, the concentration of Tb may be 5-30wt%, preferably 10.5-12.0wt%, such as 10.9wt%. The concentration of Tb indicates the percentage of the weight of Tb to the total weight of the second shell layer.
[0063] When the third shell layer includes Pr, the concentration of Pr may be 1-10wt%, preferably 3-5wt%, such as 4.4wt%. The concentration of Pr indicates the percentage of the weight of Pr to the total weight of the third shell layer.
[0064] When the third shell layer includes Nd, the concentration of Nd may be 5-30wt%, preferably 10-20wt%, such as 14.5wt%. The concentration of Nd indicates the percentage of the weight of Nd to the total weight of the third shell layer.
[0065] When the third shell layer includes Tb, the concentration of Tb may be 1-20wt%, preferably 3-6wt%, such as 5.5wt%. The concentration of Tb represents the percentage of the weight of Tb to the total weight of the third shell layer.
[0066] In the present invention, the non-rare earth elements are preferably Co and Cu; Cu and Ga; Co, Cu and Ga; or Cu and Al.
[0067] When the main phase grains include Co, the concentration of Co may be 0.5-1.5wt%, preferably 0.8-1.2wt%, such as 1.1wt%. The concentration of Co represents the percentage of the weight of Co to the total weight of the main phase grains.
[0068] When the first shell layer includes Co, the concentration of Co may be 1-10wt%, preferably 1.1-2.5wt%, for example 1.2wt%. The concentration of Co represents the percentage of the weight of Co to the total weight of the first shell layer.
[0069] When the first shell layer includes Cu, the concentration of Cu may be 0.05-0.15wt%, preferably 0.08-0.12wt%, for example 0.10wt%. The concentration of Cu represents the percentage of the weight of Cu to the total weight of the first shell layer.
[0070] When the second shell layer includes Co, the concentration of Co may be 1-10wt%, preferably 1.1-2.5wt%, for example 1.3wt%. The concentration of Co represents the percentage of the weight of Co to the total weight of the second shell layer.
[0071] When the second shell layer includes Cu, the concentration of Cu may be 0.05-0.15wt%, preferably 0.08-0.12wt%, for example 0.10wt%. The concentration of Cu represents the percentage of the weight of Cu to the total weight of the second shell layer.
[0072] When the third shell layer includes Cu, the concentration of Cu may be 0.05-0.15wt%, preferably 0.08-0.12wt%, for example 0.30wt%. The concentration of Cu represents the percentage of the weight of Cu to the total weight of the third shell layer.
[0073] When the third shell layer includes Co, the concentration of Co may be 1-10wt%, preferably 1.1-2.5wt%, such as 1.2wt%. The concentration of Co represents the percentage of the weight of Co to the total weight of the third shell layer.
[0074] In the present invention, the concentration of non-rare earth in the main phase grains may be 0.5-1.5wt%, preferably 0.8-1.2wt%, for example 1.1wt%. The concentration of non-rare earth in the first shell layer may be 0.5-1.5wt%, preferably 0.8-1.4wt%, for example 1.3wt%. The concentration of non-rare earth in the second shell layer may be 1.0-2.0wt%, preferably 1.2-1.8wt%, for example 1.4wt%. The concentration of non-rare earth in the third shell layer may be 1.0-2.0wt%, preferably 1.2-1.8wt%, for example 1.5wt%.
[0075] In the present invention, when the NdFeB main phase includes heavy rare earth elements, the concentration of the heavy rare earth elements in the NdFeB main phase preferably satisfies the following relationship: second shell layer>first shell layer>third shell layer>main phase grains.
[0076] In the present invention, when the NdFeB main phase includes light rare earth elements, the concentration of light rare earth in the NdFeB main phase preferably satisfies the following relationship: main phase grains>first shell layer>third shell layer>second shell layer.
[0077] In the present invention, the concentration of non-rare earth in the NdFeB main phase preferably satisfies the following relationship: third shell layer>second shell layer>first shell layer>main phase grains.
[0078] The present invention also provides a RTB magnet material, which comprises the following components:
[0079] R: 28.5-34.5wt.%, wherein R is a rare earth element;
[0080] M1: 1.0-2.5wt.%; the M1 includes at least two of Al, Co, Cu, Ga, Zr and Ti;
[0081] B: 0.9-1.0wt.%;
[0082] Fe: 65-70 wt.%, wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
[0083] In the present invention, R may be a heavy rare earth element and / or a light rare earth element. The light rare earth element is preferably Nd, Pr and Ce; Nd and Pr; or Nd and Ce. The heavy rare earth element is preferably Dy and / or Tb.
[0084] In the present invention, the content of R is preferably 30.0-32.5wt%, for example, 32.23wt%, 31.58wt%, 31.44wt%, 31.34wt%, 31.33wt% or 31.07wt%.
[0085] Wherein, when the R includes a light rare earth element, the content of the light rare earth element is preferably 28.5-31.5wt%, such as 31.04wt%, 30.92wt%, 30.90wt%, 29.85wt% or 29.15wt%.
[0086] When the light rare earth elements contain Nd, the content of Nd may be conventional in the art, preferably 24.3-29wt%, for example 28.85wt%, 26.05wt%, 25.95wt%, 25.94wt%, 25.92wt% or 24.83wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0087] When the light rare earth element contains Pr, the content of Pr may be conventional in the art, preferably 4.0-5.2wt%, such as 5.02wt%, 4.02wt%, 4.01wt%, 3.99wt% or 3.98wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0088] When the light rare earth element contains Ce, the content of Ce may be conventional in the art, preferably 0.2-1.2 wt%, such as 0.98 wt% or 0.3 wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0089] Wherein, when the R includes a heavy rare earth element, the content of the heavy rare earth element is preferably 0.30-2.46wt%, for example, 2.38wt%, 1.92wt%, 0.54wt%, 0.52wt%, 0.43wt% or 0.42wt%.
[0090] When the heavy rare earth element contains Dy, the content of Dy may be conventional in the art, preferably 0.1-1.6wt%, such as 1.48wt%, 0.54wt% or 0.52wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0091] When the heavy rare earth element contains Tb, the content of Tb may be conventional in the art, preferably 0.4-2.0wt%, such as 1.92wt%, 0.90wt%, 0.43wt% or 0.42wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0092] In the present invention, the M1 is preferably Al, Co, Cu, Ga and Zr; Al, Co, Cu and Ga; or Al, Co, Cu, Ga and Ti.
[0093] In the present invention, the content of M1 is preferably 1.20-2.30 wt%, for example, 1.99 wt%, 1.55 wt%, 1.37 wt%, 1.32 wt% or 1.403 wt%.
[0094] When the M1 contains Al, the content of Al may be conventional in the art, preferably 0.05-0.40wt%, such as 0.32wt%, 0.16wt%, 0.15wt% or 0.11wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0095] When M1 contains Co, the content of Co may be conventional in the art, preferably 0.10-1.50wt%, such as 1.12wt%, 0.65wt%, 0.59wt%, 0.58wt% or 0.20wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0096] When M1 contains Cu, the content of Cu may be conventional in the art, preferably 0.3-0.6 wt%, such as 0.55 wt%, 0.46 wt% or 0.45 wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0097] When Ga is contained in the M1, the content of Ga may be conventional in the art, preferably 0.05-0.50wt%, such as 0.36wt%, 0.23wt% or 0.10wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0098] When the M1 contains Zr, the content of Zr may be conventional in the art, preferably 0.05-0.15 wt %, such as 0.1 wt %, where wt % is the percentage of the total mass of the RTB magnet material.
[0099] When M1 contains Ti, the content of Ti may be conventional in the art, preferably 0.05-0.50 wt%, such as 0.36 wt% or 0.1 wt%, where wt% is the percentage of the total mass of the RTB magnet material.
[0100] In the present invention, the content of B is preferably 0.92-0.99 wt%, such as 0.98 wt%, 0.95 wt% or 0.94 wt%.
[0101] In the present invention, the Fe content is preferably 65.40-67.00wt%, for example, 66.34wt%, 66.21wt%, 66.17wt%, 66.07wt%, 66.00wt% or 65.47wt%.
[0102] In a specific embodiment, the RTB magnet material is composed of the following components: Nd 28.85wt.%, Ce 0.3wt.%, Tb 1.92wt.%, Fe 66.00wt.%, Al 0.32wt.%, Co 1.12wt.%, Cu 0.45wt.%, Ga 0.1wt.% and B 0.94wt.%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
[0103] In a specific embodiment, the RTB magnet material is composed of the following components: Nd 24.83wt.%, Pr 5.02wt.%, Dy 1.48wt.%, Tb 0.90wt.%, Fe 65.47wt.%, Al 0.11wt.%, Co 0.20wt.%, Cu 0.55wt.%, Ga 0.36wt.%, Ti 0.10wt.% and B 0.98wt.%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
[0104] In a specific embodiment, the RTB magnet material is composed of the following components: Nd 25.92wt.%, Pr4.02wt.%, Ce 0.98wt.%, Tb 0.42wt.%, Fe 66.34wt.%, Al 0.15wt.%, Co0.58wt.%, Cu0.44wt.%, Ga 0.10wt.%, Zr 0.10wt.% and B 0.95wt.%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
[0105] In a specific embodiment, the RTB magnet material is composed of the following components: Nd 25.94wt.%, Pr 3.98wt.%, Ce 0.98wt.%, Tb 0.43wt.%, Fe 66.17wt.%, Al 0.11wt.%, Co 0.65wt.%, Cu 0.46wt.%, Ga 0.23wt.%, Zr 0.10wt% and B 0.95wt.%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
[0106] In a specific embodiment, the RTB magnet material is composed of the following components: Nd 25.95wt.%, Pr 3.99wt.%, Ce 0.98wt.%, Dy 0.52wt.%, Fe 66.21wt.%, Al 0.16wt.%, Co 0.59wt.%, Cu 0.45wt.%, Ga 0.10wt.%, Zr 0.10wt.% and B 0.95wt.%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
[0107] In a specific embodiment, the RTB magnet material is composed of the following components: Nd 26.05wt.%, Pr 4.01wt.%, Ce 0.98wt.%, Dy 0.54wt.%, Fe 66.07wt.%, Al 0.16wt.%, Co 0.58wt.%, Cu 0.46wt.%, Ga 0.10wt.%, Zr 0.10wt% and B 0.95wt%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
[0108] The present invention also provides a method for preparing the RTB magnet material as described above, which comprises the following steps: attaching the RTB magnet diffusion source as described above to the surface of the RTB magnet substrate, and performing grain boundary diffusion treatment and tempering treatment.
[0109] In the present invention, the composition of the RTB magnet substrate can be conventional in the art, and preferably includes the following components:
[0110] R: 29-32wt.%, wherein R is a rare earth element;
[0111] M2: 0.8-2wt.%; the M2 comprises one or more of Al, Co, Cu, Ga, Zr and Ti;
[0112] B: 0.9-1.0wt.%;
[0113] Fe: 65-70 wt.%, wt.% is the percentage of the mass of each component in the RTB magnet substrate to the total mass of the RTB magnet substrate.
[0114] Wherein, the content of R in the RTB magnet substrate is preferably 29-31.5 wt.%, such as 30.95 wt.%, 30.93 wt.% or 29.94 wt.%.
[0115] The R in the RTB magnet substrate may be conventional in the art, and generally contains at least a light rare earth element LR. The LR preferably includes one or more of Nd, Pr and Ce, such as Nd, Pr and Ce; Nd; or Nd and Pr.
[0116] When the LR contains Nd, the content of Nd may be conventional in the art, preferably 23-32 wt.%, such as 24.98 wt.%, 25.97 wt.% or 28.96 wt.%.
[0117] When the LR contains Pr, the content of Pr may be conventional in the art, preferably 10 wt.% or less, such as 3.98 wt.% or 4.48 wt.%.
[0118] When the LR contains Ce, the content of Ce may be conventional in the art, preferably 5 wt.% or less, such as 0.98 wt.%.
[0119] The R in the RTB magnet substrate preferably further contains a heavy rare earth element HR. The type of HR can be conventional in the art, for example, including Dy and / or Tb.
[0120] When the HR contains Dy, the content of Dy is preferably 2.0 wt.% or less, for example, 1.49 wt.%.
[0121] When the HR contains Tb, the content of Tb is preferably 2.0 wt.% or less, for example 0.98 wt.%.
[0122] Wherein, in the RTB magnet substrate, the content of M2 is preferably 0.5-1.9 wt.%, such as 1.69 wt.%, 1.28 wt.% or 0.99 wt.%.
[0123] Among them, in the RTB magnet substrate, the types of M2 are preferably Al, Co, Cu, Ga and Zr; Al, Co, Cu and Ga; or Al, Co, Cu, Ga and Ti.
[0124] Wherein, in the RTB magnet substrate, when the M2 contains Al, the content of Al is preferably less than 0.5 wt.%, for example, 0.32 wt.% or 0.11 wt.%.
[0125] Wherein, in the RTB magnet substrate, when the M2 contains Co, the content of Co is preferably 0.1-1 wt.%, such as 0.2 wt.%, 0.58 wt.% or 0.97 wt.%.
[0126] Wherein, in the RTB magnet substrate, when the M2 contains Cu, the content of Cu is preferably 0.1-1 wt.%, such as 0.39 wt.%, 0.38 wt.% or 0.3 wt.%.
[0127] Wherein, in the RTB magnet substrate, when the M2 contains Ga, the content of Ga is preferably 0.1-1 wt.%, such as 0.1 wt.% or 0.2 wt.%.
[0128] Wherein, in the RTB magnet substrate, when the M2 contains Zr, the content of Zr is preferably less than 0.5 wt.%, for example, 0.1 wt.%.
[0129] Wherein, in the RTB magnet substrate, when the M2 contains Ti, the content of Ti is preferably less than 0.5 wt.%, for example, 0.1 wt.%.
[0130] Wherein, in the RTB magnet substrate, the content of B is preferably 0.9-0.99 wt.%, such as 0.94 wt.%, 0.95 wt.% or 0.98 wt.%.
[0131] Among them, those skilled in the art know that the content of Fe is generally the difference between the total mass of the RTB magnet substrate and the total mass content of other elements (R, M and B elements) in the RTB magnet substrate. The content of Fe is preferably 65-70wt.%, such as 66.84wt.%, 67.08wt.% or 67.43wt.%.
[0132] In a specific embodiment, the RTB magnet substrate is composed of the following components: Nd 28.96wt.%, Tb 0.98wt.%, Fe 67.43wt.%, Al 0.32wt.%, Co 0.97wt.%, Cu 0.3wt.%, Ga 0.1wt.% and B 0.94wt.%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet substrate.
[0133] In a specific embodiment, the RTB magnet substrate is composed of the following components: Nd 24.98wt.%, Pr4.48wt.%, Dy 1.49wt.%, Fe 67.08wt.%, Al 0.11wt.%, Co 0.2wt.%, Cu 0.38wt.%, Ga0.2wt.%, Ti 0.1wt% and B 0.98wt.%, where the mass of each component by wt.% is the percentage of the total mass of the RTB magnet substrate.
[0134] In a specific embodiment, the RTB magnet substrate is composed of the following components: Nd 25.97wt.%, Pr 3.98wt.%, Ce 0.98wt.%, Fe 66.84wt.%, Al 0.11wt.%, Co 0.58wt.%, Cu 0.39wt.%, Ga 0.1wt.%, Zr 0.1wt.% and B 0.95wt.%, where wt.% is the percentage of the mass of each component to the total mass of the RTB magnet substrate.
[0135] In the present invention, the preparation process of the RTB magnet substrate can be conventional in the art.
[0136] In some preferred embodiments, the method for preparing the RTB magnet substrate preferably comprises the following steps: subjecting a raw material mixture prepared from the components of the RTB magnet substrate to smelting, casting, fine grinding, magnetic field pressing and sintering treatments in sequence.
[0137] Among them, those skilled in the art know that the raw material composition of the RTB magnet substrate is basically the same as the components in the final RTB magnet substrate. Those skilled in the art can prepare the raw materials according to the required components of the RTB magnet substrate, and the burning loss of rare earth needs to be considered during the preparation. It should be noted that there will be changes within the error range during the preparation process.
[0138] The smelting temperature is preferably 1400-1600°C, for example 1500°C.
[0139] The vacuum degree of the smelting is preferably 5×10 -2 Pa.
[0140] The casting environment is, for example, an inert atmosphere, such as argon.
[0141] After the casting and before the fine grinding, a rapid cooling treatment is generally performed to obtain a rapidly cooled alloy. The cooling rate of the rapid cooling treatment is, for example, 10 2 ℃ / sec-10 3 °C / sec.
[0142] Among them, the fine grinding can be a conventional crushing process in the art, such as hydrogen absorption, dehydrogenation and airflow milling treatment in sequence. The pressure of the system after the hydrogen absorption is preferably maintained at 0.1-0.2MPa, for example, 0.15MPa. After the hydrogen absorption, the temperature of the system can be 500-600°C, for example, 550°C. The airflow milling treatment is preferably carried out in a nitrogen atmosphere with an oxidizing gas content of less than 150ppm. During the airflow milling treatment, the pressure of the system is preferably maintained at 0.3-0.4MPa, for example, 0.38MPa. The time of the airflow milling treatment is preferably 2-3h. After the fine grinding, the D50 of the obtained alloy can be 3-6μm.
[0143] The magnetic field strength of the magnetic field pressing molding may be 1.5-2T, for example 1.6T.
[0144] The sintering process can be carried out under vacuum conditions, for example, at 8×10 -3 The sintering is carried out under vacuum conditions of 0.03 Pa, and the sintering temperature is preferably 1000-1100°C, such as 1040-1060°C.
[0145] Wherein, the sintering treatment time can be 3-5h.
[0146] In the present invention, the size of the RTB magnet substrate can be cut according to actual needs. For example, the length is 25 mm, the width is 12 mm, the thickness is 3 mm, and the thickness direction is the magnetic field direction; another example is the length is 20 mm, the width is 12 mm, and the thickness is 2 mm; or, the length is 25 mm, the width is 12 mm, and the thickness is 2 mm; or, the length is 34 mm, the width is 18 mm, and the thickness is 8 mm.
[0147] In the present invention, the RTB magnet diffusion source is preferably an alloy powder formed from the components.
[0148] Wherein, the particle size D50 of the alloy powder is preferably 1-10 μm.
[0149] In the present invention, the attachment method may be one or more of coating, printing, dipping, coating, deposition, electroplating and sputtering, such as coating.
[0150] In the present invention, the attachment is preferably to attach the RTB magnet diffusion source on both sides of the RTB magnet substrate.
[0151] In the present invention, the amount of the RTB magnet diffusion source can be 0.5%-2.0%, such as 0.6%, 0.7%, 0.8%, 1.3%, 1.7% or 1.9%. The amount represents the percentage of the mass of the RTB magnet diffusion source to the total mass of the RTB magnet diffusion source and the RTB magnet substrate.
[0152] In the present invention, the grain boundary diffusion treatment is preferably performed in a vacuum or argon atmosphere.
[0153] In the present invention, the temperature of the grain boundary diffusion treatment is preferably 850-950°C, such as 880, 900, 920 or 940°C.
[0154] In the present invention, the time of the grain boundary diffusion treatment may be conventional in the art, and may be 5-40 hours, preferably 6-35 hours, such as 10, 20, 26 or 30 hours.
[0155] In the present invention, after the grain boundary diffusion treatment is completed, a cooling step is preferably performed. The end point of the cooling can be room temperature, generally 20-30°C.
[0156] In the present invention, the temperature of the tempering treatment is preferably 450-550°C.
[0157] In the present invention, the tempering treatment time may be 1-3 hours, for example 3 hours.
[0158] In the present invention, the vacuum degree of the tempering treatment is, for example, 8×10 -3 Pa.
[0159] The present invention also provides an application of the RTB magnetic material as described above as an electronic component in a motor.
[0160] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0161] The reagents and raw materials used in the present invention are commercially available.
[0162] The positive and progressive effects of the present invention are:
[0163] The RTB magnet material obtained by using the diffusion source of the present invention to perform grain boundary diffusion treatment on the RTB magnet substrate can form a special three-shell core structure, which includes an inner core and a shell layer covering the inner core; the inner core includes main phase grains; and the shell layer includes a first shell layer, a second shell layer and a third shell layer in sequence in a direction away from the inner core. The diffusion source can consume less rare earth elements, so that the rare earth elements are effectively utilized, thereby being able to more significantly improve the coercive force of the RTB magnet material, while maintaining the remanence basically unchanged, and further having better temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0164] Figure 1 Part a is a SEM image of the main phase of NdFeB in the RTB magnet material of Example 2 (the scale bar in the figure is 2 μm); Figure 1 Part b and part c are the surface scan results of Tb element and line scan results of each element respectively.
[0165] Figure 2 This is a SEM labeled image of the three-shell core structure of the NdFeB main phase in the RTB magnet material of Example 2 (the scale bar in the figure is 2 μm).
[0166] Figure 3 Part a is a whole surface scanning result diagram of Tb in the RTB magnet material obtained in Example 2. Figure 3 Part b is the overall surface scanning result of Tb in the RTB magnet material prepared in Comparative Example 1.
[0167] Figure 4 Part a is a surface scanning result diagram of Tb in the RTB magnet material prepared in Example 2; Figure 4 Part b is a surface scanning result of Tb in the RTB magnet material prepared in Comparative Example 1 (the scale bar in the figure is 50 μm).
[0168] Figure 5 This is a Tb line scan result diagram of the RTB magnet material of Example 2 and Comparative Example 1 from the magnet surface to the center 0-500 μm.
[0169] Figure 6 This is a surface scanning image of the core-shell structure of the RTB magnet material of Example 2.
[0170] Figure 7 This is a test chart of the shell thickness of the NdFeB main phase in the RTB magnet material of Example 2.
[0171] Figure 8 Schematic diagram of coating the RTB diffusion source on the surface of the RTB magnet substrate.
[0172] Description of reference numerals:
[0173] Main phase grain-101; first shell layer-201; second shell layer-202; third shell layer-203;
[0174] RTB magnet substrate-103; RTB diffusion source-203;
[0175] The position of the main phase grain point scan is -1; the position of the first shell point scan is -2; the position of the second shell point scan is -3; the position of the third shell point scan is -4. DETAILED DESCRIPTION
[0176] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0177] Example 1 Preparation method of R-TB magnet material
[0178] (1) Preparation of RTB magnet substrate
[0179] According to the formula of the RTB magnet substrate in Table 1, the raw materials of each component of the RTB magnet substrate are weighed, and the RTB magnet substrate is obtained by melting, casting, hydrogen crushing, air flow milling, magnetic field pressing and sintering in sequence.
[0180] Melting and casting: According to the raw material formula of the RTB magnet substrate in Table 1, the prepared matrix raw material composition was placed in an alumina crucible and smelted in a high-frequency vacuum melting furnace at 5×10 -2 The vacuum melting was carried out under the conditions of 1500°C and 1000 Pa until all the raw materials were melted. During the melting process, argon gas was introduced into the medium frequency vacuum induction rapid solidification belt spinning furnace (the vacuum degree under argon atmosphere was 5.5×10 4 Pa), rapid cooling during casting (speed of 10 2 ℃ / sec-10 3 ℃ / second), and obtain alloy sheet.
[0181] Fine grinding: (1) Hydrogen crushing powder making: The alloy sheets are placed in a hydrogen crushing furnace at room temperature. After evacuation, hydrogen with a purity of 99.9% is introduced into the furnace, and the hydrogen pressure is maintained at 0.15 MPa. After sufficient hydrogen absorption, vacuum is evacuated, the temperature is raised to 550 degrees and maintained for 2 hours to fully dehydrogenate, and then cooled to obtain powder after hydrogen crushing.
[0182] (2) Airflow milling: In a nitrogen atmosphere with an oxidizing gas content of less than 150 ppm, the powder after hydrogen crushing is subjected to airflow milling for 2-3 hours at a crushing chamber pressure of 0.38 MPa to obtain fine alloy powder with a D50 of 3-6 μm.
[0183] Magnetic field pressing molding: The fine alloy powder after air flow grinding is molded in a magnetic field strength of 1.6T.
[0184] Sintering treatment: The formed magnet is placed in a sintering furnace for sintering at 8×10 -3 The RTB magnet substrate is sintered at 1040-1060°C for 3-5h under a vacuum of 0.03 Pa.
[0185] (2) Grain boundary diffusion treatment
[0186] The diffusion source was prepared according to the formula in Table 2, and the diffusion source alloy powder (D50 particle size was 1-10 μm) was obtained by melting, casting, hydrogen pulverization and air flow milling in sequence; wherein the parameters of melting, casting, hydrogen pulverization and air flow milling were the same as those in step (1).
[0187] Grain boundary diffusion process: The RTB magnet substrate prepared above is processed into a magnet with the specifications shown in Table 2, with the thickness direction being the magnetic field orientation direction, and the surface is cleaned for use. The diffusion source prepared above is prepared into a slurry and coated on the surface of the RTB magnet substrate. The coating thickness is less than 150 μm (the schematic diagram of the coating is shown in FIG. Figure 7 The magnet is then diffused in a vacuum or argon atmosphere according to the diffusion process in Table 3. After the diffusion process is completed, it is cooled to room temperature.
[0188] Tempering treatment: The magnet after grain boundary diffusion treatment is tempered at 8×10 -3 The RTB magnet material is obtained by annealing at 450-550°C for 1-3h under a vacuum of 0.03 Pa and then cooling to room temperature after annealing.
[0189] The formulas of the RTB magnet substrate raw material compositions and diffusion sources of Examples 2-6 and Comparative Examples 1-3 are shown in Tables 1 and 2 below, and the preparation process is the same as that of Example 1.
[0190] Table 1 Formula of raw material composition of R-TB magnet substrate
[0191] Nd Pr Dy Tb Fe Al Co Cu Ga Zr Ti Ce B Example 1 29 / / 1 67.36 0.3 1 0.3 0.1 / / / 0.94 Example 2 25 4.5 1.5 / 67.02 0.1 0.2 0.4 0.2 / 0.1 / 0.98 Example 3 26 4 / / 66.75 0.1 0.6 0.4 0.1 0.1 / 1 0.95 Example 4 26 4 / / 66.75 0.1 0.6 0.4 0.1 0.1 / 1 0.95 Example 5 26 4 / / 66.75 0.1 0.6 0.4 0.1 0.1 / 1 0.95 Example 6 26 4 / / 66.75 0.1 0.6 0.4 0.1 0.1 / 1 0.95 Comparative Example 1 25 4.5 1.5 / 67.02 0.1 0.2 0.4 0.2 / 0.1 / 0.98 Comparative Example 2 26 4 / / 66.75 0.1 0.6 0.4 0.1 0.1 / 1 0.95 Comparative Example 3 26 4 / / 66.75 0.1 0.6 0.4 0.1 0.1 / 1 0.95
[0192] Note: In the above formula, the unit of each component is wt.%, which represents the percentage of the mass of each component to the total mass of the raw material composition of the RTB magnet substrate.
[0193] Table 2 Diffusion source formulation
[0194]
[0195]
[0196] Note: Specifications represent length × width × thickness; “ / ” indicates that the element is not included; In the above formula, the unit of each component is wt.%, which represents the percentage of the mass of each component to the total mass of the diffusion source.
[0197] Table 3
[0198] Grain boundary diffusion temperature (℃) Grain boundary diffusion time (h) Example 1 940 26 Example 2 880 30 Example 3 950 10 Example 4 950 10 Example 5 900 6 Example 6 900 6 Comparative Example 1 950 40 Comparative Example 2 950 10 Comparative Example 3 900 6
[0199] Effect Example 1
[0200] 1. Determination of the composition of the RTB magnet materials prepared in the examples and comparative examples
[0201] The mass content of each element in the RTB magnet substrates and RTB magnet materials prepared in the examples and comparative examples was determined using a high frequency inductively coupled plasma optical emission spectrometer (ICP-OES).
[0202] The test results of the components of the RTB magnet substrate of the embodiment are shown in Table 4. The test results of the components of the RTB magnet material of the embodiment are shown in Table 5.
[0203] Table 4
[0204]
[0205]
[0206] Note: wt.% is the percentage of the mass of each element to the total mass of the RTB magnet substrate.
[0207] Table 5
[0208] wt.% Nd Pr Dy Tb Fe Al Co Cu Ga Zr Ti Ce B Example 1 28.85 / / 1.92 66.0 0.32 1.12 0.45 0.1 / / 0.3 0.94 Example 2 24.83 5.02 1.48 0.9 65.47 0.11 0.2 0.55 0.36 / 0.1 / 0.98 Example 3 25.92 4.02 / 0.42 66.34 0.15 0.58 0.44 0.1 0.1 / 0.98 0.95 Example 4 25.94 3.98 / 0.43 66.17 0.11 0.65 0.46 0.23 0.1 / 0.98 0.95 Example 5 25.95 3.99 0.52 / 66.21 0.16 0.59 0.45 0.1 0.1 / 0.98 0.95 Example 6 26.05 4.01 0.54 / 66.07 0.16 0.58 0.46 0.1 0.1 / 0.98 0.95 Comparative Example 1 24.88 4.48 1.49 0.98 66.19 0.11 0.2 0.39 0.2 / 0.1 / 0.98 Comparative Example 2 25.79 3.91 / 0.4 64.76 0.1 1.33 1.12 0.56 0.1 / 0.98 0.95 Comparative Example 3 25.85 3.92 0.56 / 65.16 0.88 0.58 0.92 0.1 0.1 / 0.98 0.95
[0209] Note: wt.% is the percentage of the mass of each element to the total mass of the RTB magnet material.
[0210] 2. Magnetic property detection
[0211] At room temperature of 20°C, the magnetic properties of the RTB magnet substrate and the RTB magnet material were tested using a PFM pulse demagnetization curve test device (the test temperature was 20°C). The test results are shown in Table 6 below.
[0212] Here, ΔHcj refers to the value obtained by subtracting the coercive force of the corresponding RTB magnet substrate before diffusion from the coercive force of the prepared RTB magnet material.
[0213] ΔBr refers to the value obtained by subtracting the remanent magnetization of the corresponding RTB magnet substrate before diffusion from the remanent magnetization of the prepared RTB magnet material.
[0214] The mass content of Dy refers to the theoretical weight increase of Dy in the RTB magnet material after diffusion treatment.
[0215] The mass content of Tb refers to the theoretical weight increase of Tb in the RTB magnet material after diffusion treatment.
[0216] Table 6
[0217]
[0218]
[0219] It can be seen from Table 6 that, under the same substrate, compared with the comparative example 1 in which the diffusion source is TbH, the RTB magnet material prepared in Example 2 using a new diffusion source (reducing the amount of heavy rare earth) can have basically the same or even higher coercive force under the condition of equivalent remanence.
[0220] Compared with Examples 3-6, when the mass percentage of the non-metallic elements in the diffusion source is greater than 70% (such as Comparative Examples 2-3), the diffusion effect decreases sharply.
[0221] 3. High temperature performance test
[0222] The high temperature performance of RTB magnet materials was tested using the NIM-6500C permanent magnet material ultra-high temperature measurement system.
[0223] The results are shown in Table 7.
[0224] Among them, α refers to the remanence temperature coefficient of the RTB magnet material at 20-160℃ (the smaller α is, the less obvious the change of the RTB magnet material to temperature is, and the higher the reliability of the magnet is), and β refers to the coercive force temperature coefficient of the RTB magnet material at 20-160℃. The calculation formulas are as follows:
[0225]
[0226] Table 7
[0227]
[0228] It can be seen from Table 7 that, compared with Comparative Example 1, the RTB magnet material prepared in Example 1-2 has better temperature stability.
[0229] 4. Characterization of microstructure
[0230] The vertically oriented surfaces of the RTB magnet materials of Example 2 and Comparative Example 1 were polished and tested using a field emission electron probe microanalyzer (FE-EPMA) (JEOL, 8530F). The highest resolution of the FE-EPMA device is 3 nm.
[0231] (1) Element distribution
[0232] The SEM image of the main phase of NdFeB in the RTB magnet material of Example 2 is as follows: Figure 1 The corresponding Tb element surface scan and each element line scan results (scanning direction is Figure 1 The arrow directions shown in part a of FIG. Figure 1 As shown in parts b and c of Figure 1 It can be seen that the element distribution at different positions in the NdFeB main phase in the RTB magnet material is different.
[0233] The SEM marking image of the three-shell core structure of the NdFeB main phase in the RTB magnet material of Example 2 is as follows: Figure 2 As shown, Figure 2The element energy spectrum results corresponding to the point scanning of the main phase grains, the first shell, the second shell and the third shell (scanning points are 1-4 respectively) are shown in Table 8.
[0234] Table 8
[0235]
[0236]
[0237] It can be seen from Table 8 that in the NdFeB main phase of the RTB magnet material of Example 2, the heavy rare earth concentration satisfies the following relationship: 202>203>201>101, the light rare earth concentration satisfies the following relationship: 101>201>203>202, and the non-rare earth concentration satisfies the following relationship: 203>202>201>101.
[0238] Figure 3 Part a is a whole surface scanning result diagram of Tb in the RTB magnet material obtained in Example 2. Figure 3 Part b is a scanning result of the whole surface of Tb in the RTB magnet material prepared in Comparative Example 1. Figure 3 It can be seen that the NdFeB main phase of the RTB magnet material of Example 2 forms a multi-shell structure on the surface of the main phase grains, while the Tb of the RTB magnet material of Comparative Example 1 enters into the main phase grains and cannot form the aforementioned multi-shell structure.
[0239] Figure 4 Part a is a surface scanning result diagram of Tb in the RTB magnet material prepared in Example 2; Figure 4 Part b is a surface scanning result diagram of Tb in the RTB magnet material prepared in Comparative Example 1; wherein the scanning direction is from the magnet surface to the center 0-500 μm.
[0240] Figure 5 This is a Tb line scan result diagram of the RTB magnet material of Example 2 and Comparative Example 1 from the magnet surface to the center 0-500 μm.
[0241] Depend on Figure 4 and Figure 5 It can be seen that, compared with Comparative Example 1, the diffusion source of Example 2 can make the prepared RTB magnet material have a better diffusion depth under the conditions of lower diffusion temperature and shorter diffusion time.
[0242] (2) Microstructure
[0243] The surface scanning image of the core-shell structure of the RTB magnet material of Example 2 is as follows: Figure 6 shown.
[0244] Depend on Figure 6It can be seen that in the RTB magnet material of Example 2, the NdFeB main phase has a three-shell core structure, which includes an inner core and a shell layer covering the inner core; the inner core includes main phase grains 101; the shell layer includes a first shell layer 201, a second shell layer 202 and a third shell layer 203 in sequence along the direction away from the inner core.
[0245] Figure 7 This is a test chart of the shell thickness of the NdFeB main phase in the RTB magnet material of Example 2.
[0246] in, Figure 7 The a part, b part and c part of the φ are selected at three different positions. The results read from the figure are shown in Table 9.
[0247] Table 9
[0248] Figure 7 Part A Figure 7 Part B Figure 7 Part C NdFeB main phase particle size μm 11.1 14.8 5.67 The thickness of the first shell layer 201 is μm 0.83 0.65 0.80 The thickness of the second shell layer 202 is μm 2.36 2.155 1.19 Thickness of the third shell layer 203 μm 1.375 1.53 0.46
[0249] Depend on Figure 7 It can be seen that in the three shells of the NdFeB main phase in the RTB magnet material of Example 2, the thickness of the second shell is greater than the thickness of the first shell or the third shell.
[0250] The RTB magnet materials of Examples 1 and 3-6 also have a three-shell core structure similar to that of the RTB magnet material of Example 2.
Claims
1. An RTB diffusion source, characterized in that: Its composition includes alloy R a M b , R is a rare earth element; M is a non-rare earth metal element, and M includes at least two of Al, Cu, Ga, Zr, Ti and Co; a and b are the mass percentages of the corresponding elements, a=40-90wt%, b=10-60wt%.
2. The RTB diffusion source according to claim 1, characterized in that: The RTB diffusion source meets one or more of the following conditions: A, R is a heavy rare earth element and / or a light rare earth element, such as a heavy rare earth element and a light rare earth element; Wherein, the heavy rare earth element is preferably Dy and / or Tb, such as Dy and Tb; Wherein, the light rare earth element is preferably one or more of Pr, Nd and Ce, such as Ce, Nd or Pr; When R includes Dy, the content of Dy is preferably 30-80 wt.%, such as 40 wt.%, 50 wt.%, 60 wt.% or 70 wt.%; When Tb is included in R, the content of Tb is preferably 50-80wt.%, such as 60wt.% or 70wt%; When the R includes Pr, the content of Pr is preferably 10-50wt.%, such as 20wt%, 30wt% or 40wt.%; When R includes Nd, the content of Nd is preferably 5-20wt.%, such as 10wt.% or 15wt.%; When R includes Ce, the content of Ce is preferably 10-30wt.%, such as 20wt%; B. M is Co and Cu; Cu and Ga; Co, Cu and Ga; or Cu and Al; Wherein, when the M is Cu and Co, the mass ratio of Cu to Co is preferably 1:(0.5-1.5), more preferably 1:(0.8-1.2), for example 1:1; Wherein, when the M is Cu and Ga, the mass ratio of Cu to Ga is preferably 1:(0.5-1.5), more preferably 1:(0.8-1.2), for example 1:1; Wherein, when the M is Co, Cu and Ga, the mass ratio of Co, Cu and Ga is preferably (1-3): (1-3): 1, more preferably (1.5-2.5): (1.5-2.5): 1, for example 1: 1: 2; Wherein, when the M is Cu and Al, the mass ratio of Cu to Al is preferably 1:(0.5-1.5), more preferably 1:(0.8-1.2), for example 1:1; C. a is 60-80wt%, for example 70wt%; D. The value of b is 20-50wt%, such as 30wt% or 40wt%.
3. The RTB diffusion source according to claim 1, characterized in that: The RTB diffusion source meets one or more of the following conditions: A. The R satisfies one of the following: ①Ce and Tb; ②Pr and Tb; ③Tb; ④Nd and Dy; Wherein, when the R is Ce and Tb, the mass ratio of Ce to Tb is preferably 1:(2-4), for example 1:3; Wherein, when the R is Pr and Tb, the mass ratio of Pr to Tb is preferably 3:(4-6), for example 3:5; Wherein, when the R is Nd and Dy, the mass ratio of Nd to Dy is preferably 1:(6-8), for example 1:7; B. When the M includes Al, the content of Al is 5-30wt.%, for example, 10wt.%; C. When M includes Cu, the content of Cu is 5-30wt.%, such as 10wt.% or 20wt.%; D. When Ga is included in M, the content of Ga is 5-30wt.%, such as 10wt.% or 20wt.%; E. When M includes Co, the content of Co is 5-30wt.%, such as 10wt.% or 20wt.%; The above wt.% represents the percentage of the mass of each element to the total mass of the RTB magnet diffusion source.
4. An RTB magnet material, characterized in that: It includes a NdFeB main phase and a Nd-rich phase; Wherein, the main phase of NdFeB includes rare earth elements and non-rare earth elements; the mass percentage of rare earth elements in the RTB magnet material is 28.5-34.5wt.%; the mass percentage of non-rare earth elements in the RTB magnet material is 1.0-2.5wt.%; the non-rare earth elements include at least two of Al, Cu, Ga, Zr, Ti and Co; Among them, the main phase of NdFeB has a three-shell core structure, which includes an inner core and a shell covering the inner core; the inner core includes main phase grains; the shell layer includes a first shell layer, a second shell layer and a third shell layer in sequence along the direction away from the inner core; the concentration of rare earth elements in the second shell layer is greater than the concentration of rare earth elements in the third shell layer; the concentration of non-rare earth elements in the third shell layer is greater than the concentration of non-rare earth elements in the second shell layer; the concentration of non-rare earth elements in the third shell layer is greater than the concentration of non-rare earth elements in the first shell layer.
5. The RTB magnet material according to claim 4, characterized in that The RTB magnet material meets one or more of the following conditions: A. The mass percentage of rare earth elements in the RTB magnet material is 30.0-32.5wt%, such as 32.23wt%, 31.58wt%, 31.44wt%, 31.34wt%, 31.33wt% or 31.07wt%; B. The mass percentage of non-rare earth elements in the RTB magnet material is 1.20-2.30wt%, such as 1.99wt%, 1.55wt%, 1.37wt%, 1.32wt% or 1.403wt%; C. The rare earth element is a heavy rare earth element and / or a light rare earth element; the heavy rare earth element is preferably Dy and / or Tb; the light rare earth element is preferably one or more of Pr, Nd and Ce, such as Ce, Nd or Pr; Preferably, the rare earth element satisfies one of the following: ①Ce and Tb; ②Pr and Tb; ③Tb; ④Nd and Dy; Wherein, when the NdFeB main phase includes heavy rare earth elements, the concentration of the heavy rare earth elements in the NdFeB main phase preferably satisfies the following relationship: second shell layer>first shell layer>third shell layer>main phase grains; Wherein, when the NdFeB main phase includes light rare earth elements, the concentration of light rare earth in the NdFeB main phase preferably satisfies the following relationship: main phase grains>first shell>third shell>second shell; When the NdFeB main phase includes heavy rare earth, the concentration of heavy rare earth in the main phase grains is preferably 0.05-0.15wt%, more preferably 0.08-0.12wt%, for example 0.10wt%; the concentration of heavy rare earth in the first shell layer is preferably 1-20wt%, more preferably 1.5-1.8wt%, for example 1.7wt%; the concentration of heavy rare earth in the second shell layer is preferably 5-30wt%, more preferably 10.5-12.0wt%, for example 10.9wt%; the concentration of heavy rare earth in the third shell layer is preferably 1-20wt%, more preferably 3-6wt%, for example 5.5wt%; When the NdFeB main phase includes light rare earth, the concentration of light rare earth in the main phase grains is preferably 20-30wt%, preferably 23-28wt%, for example 25.7wt%; the concentration of light rare earth in the first shell layer is preferably 5-30wt%, more preferably 20-28wt%, for example 22.4wt%; the concentration of light rare earth in the second shell layer is preferably 5-20wt%, more preferably 10-20wt%, for example 13.6wt%; the concentration of light rare earth in the third shell layer is preferably 5-30wt%, more preferably 10-20wt%, for example 18.9wt%; When the main phase grains include Pr, the concentration of Pr is preferably 1-10wt%, more preferably 4-8wt%, for example 5.4wt%; when the main phase grains include Nd, the concentration of Nd is preferably 5-30wt%, more preferably 20-28wt%, for example 20.3wt%; when the main phase grains include Tb, the concentration of Tb is preferably 0.05-0.15wt%, more preferably 0.08-0.12wt%, for example 0.10wt%; the concentrations of Pr, Nd, and Tb respectively represent the percentage of the weight of Pr, Nd, and Tb in the total weight of the main phase grains; When the first shell layer includes Pr, the concentration of Pr is preferably 1-10wt%, more preferably 4-8wt%, for example 5.5wt%; when the first shell layer includes Nd, the concentration of Nd is preferably 5-30wt%, more preferably 10-20wt%, for example 16.9wt%; when the first shell layer includes Tb, the concentration of Tb is preferably 1-20wt%, more preferably 1.5-1.8wt%, for example 1.7wt%; the concentrations of Pr, Nd and Tb respectively represent the percentage of the weight of Pr, Nd and Tb in the total weight of the first shell layer; When the second shell layer includes Pr, the concentration of Pr is preferably 1-10wt%, more preferably 5-9wt%, for example 5.4wt%; when the second shell layer includes Nd, the concentration of Nd is preferably 1-10wt%, more preferably 5-9wt%, for example 8.2wt%; when the second shell layer includes Tb, the concentration of Tb is preferably 5-30wt%, more preferably 10.5-12.0wt%, for example 10.9wt%; the concentrations of Pr, Nd and Tb respectively represent the percentage of the weight of Pr, Nd and Tb in the total weight of the second shell layer; When the third shell layer includes Pr, the concentration of Pr is preferably 1-10wt%, more preferably 3-5wt%, for example 4.4wt%; when the third shell layer includes Nd, the concentration of Nd is preferably 5-30wt%, more preferably 10-20wt%, for example 14.5wt%; when the third shell layer includes Tb, the concentration of Tb is preferably 1-20wt%, more preferably 3-6wt%, for example 5.5wt%; the concentrations of Pr, Nd and Tb respectively represent the percentage of the weight of Pr, Nd and Tb in the total weight of the third shell layer; D. The non-rare earth elements are Co and Cu; Cu and Ga; Co, Cu and Ga; or Cu and Al; E. The concentration of non-rare earth in the NdFeB main phase satisfies the following relationship: the third shell layer> the second shell layer> the first shell layer> the main phase grains; F. When the main phase grains include Co, the concentration of Co is 0.5-1.5wt%, preferably 0.8-1.2wt%, for example 1.1wt%; the concentration of Co represents the percentage of the weight of Co to the total weight of the main phase grains; G. When the first shell layer includes Co, the concentration of Co is 1-10wt%, preferably 1.1-2.5wt%, such as 1.2wt%; when the first shell layer includes Cu, the concentration of Cu is preferably 0.05-0.15wt%, more preferably 0.08-0.12wt%, such as 0.10wt%; the concentrations of Co and Cu represent the percentage of the weight of Co and Cu to the total weight of the first shell layer; H. When the second shell layer includes Co, the concentration of Co is 1-10wt%, preferably 1.1-2.5wt%, such as 1.3wt%; when the second shell layer includes Cu, the concentration of Cu is preferably 0.05-0.15wt%, more preferably 0.08-0.12wt%, such as 0.10wt%; the concentrations of Co and Cu represent the percentage of the weight of Co and Cu to the total weight of the second shell layer; I. When the third shell layer includes Cu, the concentration of Cu is 0.05-0.15wt%, preferably 0.08-0.12wt%, for example 0.30wt%; when the third shell layer includes Co, the concentration of Co is preferably 1-10wt%, more preferably 1.1-2.5wt%, for example 1.2wt%; the concentrations of Co and Cu represent the percentage of the weight of Co and Cu to the total weight of the third shell layer; J. The thickness of the shell layer satisfies the following relationship: the second shell layer> the first shell layer or the third shell layer; K. The thickness of the first shell layer is 0.1-2 μm, preferably 0.5-1.5 μm, for example 0.83, 0.65 or 0.80 μm; L, the thickness of the second shell layer is 0.5-5 μm, preferably 1-3 μm, for example 2.36, 2.155 or 1.19 μm; M, the thickness of the third shell layer is 0.2-5 μm, preferably 0.4-2.0 μm, for example 1.375, 1.53 or 0.46 μm; N. The particle size of the NdFeB main phase is 5-15 μm, for example 5.67, 11.1 or 14.8 μm; O. The concentration of non-rare earth in the main phase grains is 0.5-1.5wt%, preferably 0.8-1.2wt%, for example 1.1wt%; P, the concentration of non-rare earth in the first shell layer is 0.5-1.5wt%, preferably 0.8-1.4wt%, for example 1.3wt%; Q. The concentration of non-rare earth in the second shell layer is 1.0-2.0wt%, preferably 1.2-1.8wt%, for example 1.4wt%; R, the concentration of non-rare earth in the third shell layer is 1.0-2.0wt%, preferably 1.2-1.8wt%, for example 1.5wt%; S, the concentration of rare earth elements in the main phase grains is 22-27wt%, preferably 25-26wt%, for example 25.8wt%; T. The concentration of the rare earth element in the first shell layer is 22-27wt%, preferably 23-25wt%, for example 24.1wt%; U. The concentration of the rare earth element in the second shell layer is 22-27wt%, preferably 23-25wt%, for example 24.5wt%; V. The concentration of the rare earth element in the third shell layer is 22-27wt%, preferably 23-25wt%, for example 24.4wt%.
6. An RTB magnet material, characterized in that: It includes the following components: R: 28.5-34.5wt.%, wherein R is a rare earth element; M1: 1.0-2.5wt.%; the M1 includes at least two of Al, Co, Cu, Ga, Zr and Ti; B: 0.9-1.0wt.%; Fe: 65-70 wt.%, wt.% is the percentage of the mass of each component to the total mass of the RTB magnet material.
7. The RTB magnet material according to claim 6, characterized in that The RTB magnet material meets one or more of the following conditions: A. R is a heavy rare earth element and / or a light rare earth element; the light rare earth element is preferably Nd, Pr and Ce; Nd and Pr; or Nd and Ce; the heavy rare earth element is preferably Dy and / or Tb; B. The content of R is 30.0-32.5wt%, such as 32.23wt%, 31.58wt%, 31.44wt%, 31.34wt%, 31.33wt% or 31.07wt%; Wherein, when the R comprises a light rare earth element, the content of the light rare earth element is preferably 28.5-31.5wt%, such as 31.04wt%, 30.92wt%, 30.90wt%, 29.85wt% or 29.15wt%; Wherein, when the light rare earth element contains Nd, the content of Nd is preferably 24.3-29wt%, such as 28.85wt%, 26.05wt%, 25.95wt%, 25.94wt%, 25.92wt% or 24.83wt%, where wt% is the percentage of the total mass of the RTB magnet material; Wherein, when the light rare earth element contains Pr, the content of Pr is preferably 4.0-5.2wt%, such as 5.02wt%, 4.02wt%, 4.01wt%, 3.99wt% or 3.98wt%, where wt% is the percentage of the total mass of the RTB magnet material; Wherein, when the light rare earth element contains Ce, the content of Ce is preferably 0.2-1.2wt%, such as 0.98wt% or 0.3wt%, where wt% is the percentage of the total mass of the RTB magnet material; Wherein, when the R comprises a heavy rare earth element, the content of the heavy rare earth element is preferably 0.30-2.46wt%, such as 2.38wt%, 1.92wt%, 0.54wt%, 0.52wt%, 0.43wt% or 0.42wt%; Wherein, when the heavy rare earth element contains Dy, the content of Dy is preferably 0.1-1.6wt%, such as 1.48wt%, 0.54wt% or 0.52wt%, where wt% is the percentage of the total mass of the RTB magnet material; Wherein, when the heavy rare earth element contains Tb, the content of Tb is preferably 0.4-2.0wt%, such as 1.92wt%, 0.90wt%, 0.43wt% or 0.42wt%, where wt% is the percentage of the total mass of the RTB magnet material; B. M1 is Al, Co, Cu, Ga and Zr; Al, Co, Cu and Ga; or Al, Co, Cu, Ga and Ti; C. The content of M1 is 1.20-2.30wt%, for example, 1.99wt%, 1.55wt%, 1.37wt%, 1.32wt% or 1.403wt%; D. When Al is contained in the M1, the content of Al is 0.05-0.40wt%, such as 0.32wt%, 0.16wt%, 0.15wt% or 0.11wt%, where wt% is the percentage of the total mass of the RTB magnet material; E. When M1 contains Co, the content of Co is 0.10-1.50wt%, such as 1.12wt%, 0.65wt%, 0.59wt%, 0.58wt% or 0.20wt%, where wt% is the percentage of the total mass of the RTB magnet material; F. When M1 contains Cu, the content of Cu is 0.3-0.6wt%, such as 0.55wt%, 0.46wt% or 0.45wt%, where wt% is the percentage of the total mass of the RTB magnet material; G. When Ga is contained in the M1, the content of Ga is 0.05-0.50wt%, such as 0.36wt%, 0.23wt% or 0.10wt%, where wt% is the percentage of the total mass of the RTB magnet material; H. When the M1 contains Zr, the content of Zr is 0.05-0.15wt%, for example, 0.1wt%, where wt% is the percentage of the total mass of the RTB magnet material; I. When M1 contains Ti, the content of Ti is 0.05-0.50wt%, such as 0.36wt% or 0.1wt%, where wt% is the percentage of the total mass of the RTB magnet material; J. The content of B is 0.92-0.99wt%, such as 0.98wt%, 0.95wt% or 0.94wt%; K. The content of Fe is 65.40-67.00wt%, for example, 66.34wt%, 66.21wt%, 66.17wt%, 66.07wt%, 66.00wt% or 65.47wt%.
8. A method for preparing an RTB magnet material, characterized in that: It includes the following steps: The RTB magnet diffusion source according to any one of claims 1 to 3 is attached to the surface of the RTB magnet substrate, and a grain boundary diffusion treatment and a tempering treatment are performed.
9. The method for preparing the RTB magnet material according to claim 8, characterized in that: The preparation method of the RTB magnet material meets one or more of the following conditions: A. The composition of the RTB magnet substrate includes the following components: R: 29-32wt.%, wherein R is a rare earth element; M2: 0.8-2wt.%; the M2 comprises one or more of Al, Co, Cu, Ga, Zr and Ti; B: 0.9-1.0wt.%; Fe: 65-70 wt.%, wt.% is the percentage of the mass of each component in the RTB magnet substrate to the total mass of the RTB magnet substrate; B. The attachment method is one or more of coating, printing, dipping, coating, deposition, electroplating and sputtering, such as coating; C. The amount of the RTB magnet diffusion source is 0.5%-2.0%, such as 0.6%, 0.7%, 0.8%, 1.3%, 1.7% or 1.9%; the amount represents the percentage of the mass of the RTB magnet diffusion source to the total mass of the RTB magnet diffusion source and the RTB magnet substrate; D. The temperature of the grain boundary diffusion treatment is 850-950°C, for example, 880, 900, 920 or 940°C; E. The grain boundary diffusion treatment time is 5-40 hours, preferably 8-35 hours, such as 20, 26 or 30 hours; F. The temperature of the tempering treatment is 450-550°C; G. The tempering time is 1-3h, for example 3h; H. The vacuum degree of the tempering treatment is 8×10 -3 Pa.
10. Use of the RTB magnetic material according to any one of claims 4 to 7 as an electronic component in a motor.
Citation Information
Patent Citations
Low-weight rare earth magnet and manufacturing method
CN113871122A
Grain boundary diffusion material, neodymium-iron-boron magnet material and preparation method and application of neodymium-iron-boron magnet material
CN115881377A
Grain boundary diffusion material, R-T-B magnet and preparation method of R-T-B magnet
CN116403792A
Low-melting-point alloy neodymium iron boron grain boundary diffusion source and coating method thereof
CN118231132A
R-t-b sintered magnet and preparation method thereof
US20210343459A1
Cited By
Heavy-rare-earth-free low-boron sintered neodymium iron boron permanent magnet and preparation method thereof
CN121709402A